2023
DOI: 10.1073/pnas.2219573120
|View full text |Cite
|
Sign up to set email alerts
|

Sensing prior constraints in deep neural networks for solving exploration geophysical problems

Abstract: One of the key objectives in geophysics is to characterize the subsurface through the process of analyzing and interpreting geophysical field data that are typically acquired at the surface. Data-driven deep learning methods have enormous potential for accelerating and simplifying the process but also face many challenges, including poor generalizability, weak interpretability, and physical inconsistency. We present three strategies for imposing domain knowledge constraints on deep neural networks (DNNs) to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…In general, prior constraints are applied to DNNS to improve the generalizability, interpretability and physical consistency of the model, including three general strategies: imposing constraints on data, fusing constraints into network architecture, and integrating constraints into loss functions (Wu et al, 2023). As an objective function related to network parameters, Eq.…”
Section: Data and Model Dual-driven Seismic Data Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, prior constraints are applied to DNNS to improve the generalizability, interpretability and physical consistency of the model, including three general strategies: imposing constraints on data, fusing constraints into network architecture, and integrating constraints into loss functions (Wu et al, 2023). As an objective function related to network parameters, Eq.…”
Section: Data and Model Dual-driven Seismic Data Reconstructionmentioning
confidence: 99%
“…During the research process, we can see that it has been difficult to achieve the goal of AI seismic exploration with a single route or paradigm. Wu et al (Wu et al, 2023) concluded that domain knowledge constraints can be applied to deep neural networks to improve those with weak generalization ability, low interpretability and poor physical consistency, such as physics-driven intelligent seismic processing (Pham and Li, 2022), impedance inversion (Yuan et al, 2022), porosity prediction (Sang et al, 2023), designing priorconstraint network architectures for seismic waveform inversion (Sun et al, 2020) and exploring the physics-informed neural network (PINN) for solving geophysical forward modeling (Song and Wang, 2023). From these studies, we conclude that a more reasonable direction to deal with reconstruction problems can be the combination of data-driven model and mechanism model.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated the effectiveness of domain adaptation by applying it to seismic imaging problems. Wu et al [33] proposed to integrate domain knowledge to impose prior constraints for geophysical problems, which can improve the generalizability and interpretability of DNN models.…”
Section: Introductionmentioning
confidence: 99%
“…However, starting in the second decade of the 2000s, a new era of HPC has developed thanks to the arrival of the new graphic processing units (GPU), its high parallelization capacity, and easy access outside the business or academic field due to its low cost. The most commonly used techniques in geophysics have focused mainly on electromagnetic and seismic methods and can be generally classified as parallelization of numerical methods [55][56][57][58][59][60][61], based on neural networks and deep learning [62][63][64][65], and more recently, based on quantum computing [66].…”
Section: Introductionmentioning
confidence: 99%